Faktor-Faktor yang Mempengaruhi Kecemasan Mahasiswa Keperawatan Semester Awal Sebelum Ujian Skill Laboratory - Annisa, Nur; Dewi, Yulia Irvani; Zulfitri, Reni (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2023)
Laboratory skill is one of the factors that cause anxiety for students. This study aims to determine the factors that influence the anxiety of nursing students in the first semester before the laboratory skill. This study used a cross sectional study approach. This study used a sample of 112 respondents who were taken using a purposive sampling technique and had inclusion criteria. This study used bivariate analysis with chi-square test. There are 65 respondents who have a low level of anxiety (58%), 47 respondents have a high level of anxiety (42%). The results of statistical tests carried out on 2 factors resulted in an influence between the environment and anxiety levels in early semester nursing students with p value (0.000) < alpha (0.05) and there was an influence between knowledge level and anxiety level in early semester nursing students with p value (0.000) < alpha (0.05). Environmental atmosphere and knowledge have a significant influence on the level of anxiety in nursing students in the first semester before the laboratory skill test.